The Relationship Between Students' Interpersonal Communication to Other People and Bullying Behavior in High School - Layli, Lukman (Yayasan Mata Pena Madani, 2025)
This study aims to determine the relationship of student’s interpersonal communication toward bullying behavior especially in high school students. This research method using the correlational quantitative with a total of 199 subjects in high school. interpersonal communication measured by Devito's scale and bullying was measured by Coloroso's scale. The data analysis technique used in this study is the Pearson product moment correlation. According to data statistic the results of the analysis shown that Pearson correlation r = -0.315 (p 0.05) that is means result is significantly negative between interpersonal communication toward student bullying behavior, which means that the higher interpersonal communication of students with others, the lower bullying behavior happened in high school.